Investigating The Role Of Taste, Price, And Marketing Methods On Consumer Purchasing Decisions On Flavored Ice Cube Products - Riesta Devi Kumalasari (Tourism Department, State Polytechnic of Banyuwangi, 2023)
The purpose of this study is to determine the influence of taste, price, and marketing methods on consumer purchasing decisions on flavored ice cube products. This research was conducted using quantitative research methods with data obtained through the distribution of questionnaires to 100 respondents. Analysis of the data obtained was carried out by data analysis techniques using the SPSS application by pouring the results of questionnaires distributed by researchers. The result of this study is that taste, price, and marketing methods have a large and significant influence on consumer purchasing decisions. Consumers want products that have prices by the taste offered, and the taste of a product must be consistent to cause purchase repetition and loyalty from consumers. Marketing for products is considered more relevant through social media, where social media is used as a place for interaction and exchange of information, so digital marketing is the right thing. It is hoped that this research can be a guide to help businesses or similar businesses determine their strategies in terms of taste, price, and marketing methods in their business.